Disiplin Berlalu Lintas Pada Remaja Pengendara Sepeda Motor - Ridho, Habid, Rini Lestari, S.Psi, M.Si (2016)
The phenomenon of traffic discipline in developing countries like Indonesia is quite alarming. This research aims to know traffic discipline on motorists in their teens, where at the age of adolescence is a time of emotional development and concerned with the Summit itself. This research was conducted on 119 students in SMK Muhammadiyah 1 Surakarta at 2nd grade. The methods used in this research was the qualitative approach method of Phenomenology. Data collected using questionnaires and interviews while the analysis uses the analysis of content. From the results of the study revealed that the attitude of traffic discipline in teenagers at 2nd grade CMS less discipline, students know what good traffic stance i.e. obey traffic signs and respect other riders. But in fact the students often violate traffic rules because of the rush and traffic facilities are not functioning so that students do not obey the traffic code of conduct. Many students who do not yet have a DRIVER'S LICENSE because of insufficient age, does not yet have a cost, and not knowing information how to make driver's licence from at who already has a driver's licence. Factors that affect students when the drive is twofold, internal factors and external factors. Internal factors include the physical condition of the rider and the external factor includes road conditions at the time of heavy rain until the road becomes slick, hollow road, when raids by the police, the attitude of the other riders, animal crossing, and in a hurry when heading off to school Key words : traffic Discipline, driving license, driving, hollow road.